Examples:
 Simplify, x^{5} * x^{3} * x^{4}.
Given that, x^{5} * x^{3} * x^{4}
Using x^{m} * x^{n} = x^{m+n}
We get, x^{5+34}
= x^{4}
 Simplify, ((x^{4})^{2})^{2}.
Given that, ((x^{4})^{2})^{2}
Using, ((a^{m})^{n})^{p} = (a^{m})^{np} = a^{mnp}
((x^{4})^{2})^{2} = (x^{4})^{2*2}
= (x^{4})^{4}
= x^{4*4}
= x^{16}.
 Simplify, x^{8}/x^{4}.
Given that, x^{8}/x^{4}
Using, x^{m}/x^{n} = x^{mn}
x^{8}/x^{4} = x^{84}
= x^{4}
Directions: Solve the following problems. Also write at least 10 examples of your own.
